Design and Development of a Waste Reporting and Monitoring Application to Reduce Open Dumping in Ternate City - Yasir Muin; Salkin Lutfi (JATISI, 2025)
Waste management remains one of the most pressing environmental challenges in many regions, including Ternate City. The persistent practice of open dumping has led to severe environmental and public health impacts. This study aims to design and develop a Waste Reporting and Monitoring Application as a technology-based solution to enhance community participation and improve waste management effectiveness. The system was developed using the Prototype Method, allowing iterative development through continuous user feedback to ensure the final product meets actual needs. The application was built using the Laravel framework and modeled through a Use Case Diagram to represent user interactions within the system. Testing with the Black Box method confirmed that all system functions operated effectively, including report submission, photo uploads, and real-time monitoring. The implementation of this application has increased community engagement in reporting waste accumulation and assisted local authorities in responding more efficiently and systematically. Therefore, the system is expected to serve as a concrete step toward reducing open dumping practices and promoting sustainable environmental management in Ternate City